Posterior Circulation ASPECTS on CT Angiography Predicts Futile Recanalization of Endovascular Thrombectomy for Acute Basilar Artery Occlusion - Ouyang, Keni; Kang, Zhiming; Liu, Zhengxing; Hou, Botong; Fang, Jiabing; Xie, Yu; Liu, Yumin (Frontiers in Neurology, 2022)
BACKGROUND: Acute basilar artery occlusion (BAO) is the most potentially disastrous outcome and high risk of recurrence stroke in posterior circulation infarction (PCI). However, the rate of futile recanalization remains high despite successful recanalization. The objective of this study was to investigate 90 days functional outcomes among BAO patients who underwent EVT and to identify the risk factors associated with futile recanalization. METHODS: We retrospectively analyzed 72 patients with acute BAO who received EVT from January 2018 to June 2021. CTA-SI pc-ASPECTS evaluated the extensive hypo-attenuation in BAO patients. Poor outcome defined mRS of 3-6 at 90 days despite a successful recanalization. Use logistic regression to evaluated risk factors related to futile recanalization. RESULTS: Our sample included a total of 55 eligible patients. Patients with poor outcomes showed the pc-ASPECTS score was lower in patients with poor outcome than that in patients with good outcome (P=0.017), longer time from symptoms onset-to-the puncture (P=0.014), and elevation of leucocytes (P=0.012) were associated with poor outcome. Multivariable logistic analysis showed pc-ASPECTS and onset-to-puncture time were independent predictors of futile recanalization. CONCLUSIONS: This study suggested that pc-ASPECTS and onset-to-puncture time are independent predictors of futile recanalization after EVT in BAO patients. The lower pc-ASPECTS score and longer puncture time will have poor clinical outcome. The prophylactic use of antibiotics with extensive cerebral ischemia of BAO patients to reduce poor prognosis.